DIFFERENCES IN THE READING COMPREHENSION ABILITY OF STUDENTS IN THE PQ4R LEARNING MODEL FOR INDONESIAN LANGUAGE SUBJECTS - Puji Rahmawati; Hamdiah Susanti; Yulia Deodata Selestin; Amin Mustajab (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2020)
The purpose of this research is to determine students' reading comprehension skills before and after using the PQ4R learning model. This research was motivated by preliminary studies, which showed that students' reading comprehension skills are still low in conventional learning models. This is a quantitative research consisting of a one-group pretest-posttest research design. Data were obtained from 22 students of state elementary school 03 Sontas using a written test of 6 (six) questions. The research showed differences in students' reading comprehension skills before and after learning using the PQ4R model.